Recurrent urethral obstruction secondary to large vulval inclusion cyst: a remote complication of female genital mutilation: a case report - AbdelAziem A. Ali; Israa Badreldin (BMC, 2023)
Abstract Background Female genital mutilation/cutting (FGM/C) is a major public health problem, particularly in developing countries. Case presentation The authors reported a case of 48-year old multiparous woman presented to Kassala Hospital, east Sudan, with recurrent urine retention resulting from urethral obstruction, which was caused by large vulval inclusion cyst. A traditional birth attendant circumcised her when she was 5 year old. Five years before her presentation the patient observed a painless swelling in her vulva, which was gradually increasing in size. She presented to the hospital with urine retention seeking medical care. Local examination showed a large cystic swelling originating in the circumcision line and covering the introitus. A diagnosis of inclusion cyst at the site of circumcision was made. The cyst was large enough causing bladder outlet obstruction and when the patient advised to tilt it away from the urethral orifice she passed urine without difficulties. The cyst was surgically removed by dissection along the lines of cleavage, which measured 10 × 9.2 cm and weighed 1.2 kg. Conclusion This case report indicates that FGM is a serious public health problem and there should an urgent intervention such as planned health education campaigns to end FGM practice.